A Bibliometric Study on E-Learning Software Engineering Education - Benabdelouahab, Soukaina; García-Berná, José A.; Moumouh, Chaimae; Carrillo-de-Gea, Juan M.; El Bouhdidi, Jaber; El Younoussi, Yacine; Fernández-Alemán, José L. (J.UCS (Annual print and CD-ROM archive ed.), 2023)
Due to the substantial development of information and communications technology, the use of E-learning in higher education has become essential to boost teaching methods and enhance students' learning skills and competencies. E-learning in Software Engineering turns out to be increasingly interesting for scholars. In fact, researchers have worked to enhance modern Software Engineering education techniques to meet the required educational objectives. The aim of this article is to analyse the scientific production on E-learning Software Engineering education by conducting a bibliometric analysis of 10,603 publications, dating from 1954 to 2020 and available in the Scopus database. The results reveal some scientific production information, such as the temporal evolution of the publications, the most prolific authors, institutions and countries, as well as the languages used. Besides, the paper evaluates additional bibliometric parameters, including the authors' production, journal productivity, and scientific cooperation, among other bibliometric parameters. The subject of the current study has not been treated by any previous bibliometric studies. Our research is deeper and more specific; it covers a long period of 66 years and a large number of publications, thanks to the chosen search string containing the different spellings of the used terms. In addition, the literature is analysed using several tools such as Microsoft Excel, VOSviewer, and Python. The research findings can be used to identify the current state of E-learning Software Engineering Education, as well as to identify various research trends and the general direction of E-learning research.